GAMBARAN FAKTOR RESIKO PENYAKIT KARDIOVASKULER DI GEREJA HKBP VILLA DUTA BOGOR JULI 2023 - Nataprawira, Sari Mariyati Dewi; Sugiarto, Hans; Warsito, Jonathan Hadi; Mashadi, Fladys Jashinta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Currently, non-communicable diseases (NCDs) are of particular concern to the government, because they are the highest cause of death throughout the world in general, in Indonesia in particular. Cardiovascular diseases such as coronary heart disease and Cerebrovascular disease are the highest cases among other NCDs. Hypertension, diabetes, hyperlipidemia and hyperuricemia are risk factors for cardiovascular disease. Life style like lack of activity, high fat, calorie and tasty foods consumption are factors that increase the occurrence of NCDs. Bogor, with around 123 million population, in 2020 found of 53,635 cases of hypertension and 19,694 diabetes mellitus. This incidens is higher compared to 2019 data and will increase every year. HKBP Church, Villa Duta, Bogor City, with a congregation of 154 families, is also who are at risk of experiencing cardiovascular disease. Church leaders want to help the government in reducing the incidence of NCDs with starting by holding free examinations for congregants and local residents. The aim of this activity is to obtain an overview of the risk factors in church congregations and local residents so that education can then be provided according to the results of the examination. The method of PKM activities is to carry out blood pressure checks, capillary blood tests in blood sugar, cholesterol and uric acid level. Results: There were 70 participants who underwent the examination, 71.4% were female, 57.1% blood pressure examination were high, 44.9% blood sugar level are high and 62.9% uric acid level within normal limits. Conclusion The HKBP church congregation and surrounding residents are at risk of developing cardiovascular disease, especially if they do not change their lifestyle.